Evaluasi Program Praktek Kerja Lapangan Dengan Model Countenance Stake di SMKN 1 Suruh - Aristiawan Aristiawan; Bactiar S Bachri (Journal on Education, 2023)
The development of solving skills that are trained comprehensively from an early age in the learning process is expected to be able to produce competency standards required in national education. A number of studies on the impact of developing problem solving skills show that students are able to be successful in learning inside and outside the classroom. The implementation of street vendors at SMKN 1 Suruh in 2022 which was evaluated using the Countenance Stake model showed results in the very good category with an achievement score of 88.71%. The three components that are the focus of research are in the very good category, but have not yet reached a maximum score of 100% so that they require follow-up in efforts to improve the quality of the street vendors' implementation process as well as following up on the results obtained after participating in street vendors and continuing the implementation of knowledge and skills post street vendors in accordance with the substance of the material received.